The Effect of Compost and Biochar Fertilizers on The Growth and Yield of Shallots - I Gusti Bagus Udayana; Yohanes Parlindungan Situmeang; Robinson Ama Dangu Ngindi (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2022)
This study aims to determine the effect of compost and biochar doses and their interactions on the growth and yield of shallots. This research was conducted at the Local Waste Processing Site (TOSS), Kusamba Village, Dawan District, Klungkung Regency, Bali Province. The design used in this study was a factorial randomized block design (RAK) consisting of 2 factors. The first factor is the treatment of compost dose (K) which consists of 3 levels, namely: K1 = 5 tons ha-1, K2 = 10 tons ha-1, and K3 = 15 tons ha-1. While the second factor is the dose of biochar (B) which consists of 3 levels, namely: B1 = 5 tons ha-1, B2 = 10 tons ha-1, and B3 = 15 tons ha-1. The interaction between compost treatment with biochar had a significant (P<0.05) effect on the fresh weight of tubers per clump and fresh weight of rhizomes per clump, and a very significant effect (P<0.01) on the number of tubers per clump, but not significant (P≥0.05) to other variables. The compost dose treatment had no significant effect (P≥0.05) on all observed variables except for the maximum number of leaves. Biochar dose treatment had a significant to a very significant effect on the variables of maximum leaf number, fresh weight of tubers per clump, the oven-dry weight of tubers per clump, and oven-dry weight of tubers per clump, and had no significant effect (P≥0.05) on other variables. The interaction between compost 5 tons ha-1 and biochar 10 tons ha-1 (K1B2) gave the highest fresh weight of tubers per clump of 100.00 g which was significantly different or increased by 38.60% compared to the lowest fresh weight of tubers per clump at the interaction of compost 5 tons ha-1 with biochar 15 tons ha-1 (K1B3) is 72.15 g.